Edukacja w popkulturze – tematyka śmierci w tekstach kultury popularnej kierowanej do dzieci - Maciaszek, Piotr (Studia Edukacyjne, 2024)
The article analyses the theme of death in popular culture texts aimed at children, highlighting its educational potential. The author examines how various works of culture, such as the film Coco, and the books Wszędzie i we wszystkim and Żegnaj niedźwiadku, depict death, the mourning process and perform a thanato-educational function. The author highlights the role of popular culture in familiarizing children with death and the mourning process, pointing out its functions: familiarizing, strengthening, and normalizing. The cultural texts analyzed help children understand the complexity of these topics, normalize difficult emotions, and offer support in coping with loss. The main conclusion of the article is that cultural content, such as films and children’s books, can be a valuable tool in thanato-education, helping young audiences to understand and accept the finiteness of human existence. At the same time, it is emphasized that these texts do not provide ready answers but rather inspire individual reflection on the meaning of life and death.